Multilevel En Bloc Spondylectomy for Tumors of the Thoracic and Lumbar Spine Is Challenging But Rewarding. Issue 3 (March 2015) - Luzzati, Alessandro Davide; Shah, Sambhav; Gagliano, Fabio; Perrucchini, Giuseppe; Scotto, Gennaro; Alloisio, Marco
Abstract: Background: Over the years, en bloc spondylectomy has proven its efficacy in controlling spinal tumors and improving survival rates. However, there are few reports of large series that critically evaluate the results of multilevel en bloc spondylectomies for spinal neoplasms. Questions/purposes: Using data from a large spine tumor center, we answered the following questions: (1) Does multilevel total en bloc spondylectomy result in acceptable function, survival rates, and local control in spinal neoplasms? (2) Is reconstruction after this procedure feasible? (3) What complications are associated with this procedure? (4) is it possible to achieve adequate surgical margins with this procedure? Methods: We retrospectively investigated 38 patients undergoing multilevel total en bloc spondylectomy by a single surgeon (AL) from 1994 to 2011. Indications for this procedure were primary spinal sarcomas, solitary metastases, and aggressive primary benign tumors involving multiple segments of the thoracic or lumbar spine. Patients had to be medically fit and have no visceral metastases. Analysis was by chart and radiographic review. Margin quality was classified into intralesional, marginal, and wide. Radiographs, MR images, and CT scans were studied for local recurrence. Graft healing and instrumentation failures at subsequent followup were assessed. Complications were divided into major or minor and further classified as intraoperative and early and late postoperative. We evaluated the oncologic status using cumulative disease‐specific and metastases‐free survival analysis. Minimum followup was 24 months (mean, 39 months; range, 24‐124 months). Results: Of the 38 patients, 34 (89%) were alive and walking without support at final followup. Thirty‐one (81%) had no evidence of disease. Two patients died postoperatively and another two died of systemic disease (without local recurrence). Only three patients (8%) had a local recurrence. There were 14 major complications and 22 minor complications in 25 patients (65%). Only one patient required revision of implants secondary to mechanical failure. Two cases of cage subsidence were noted but had no clinical significance. Wide margins were achieved in nine patients (23%), marginal in 25 (66%), and intralesional in four (11%). Conclusions: In patients with multisegmental spinal tumors, oncologic resections were achieved by multilevel en bloc spondylectomy and led to an acceptable survival rate with reasonable local control. Multilevel en bloc surgery was associated with a high complication rate; however, most patients recovered from their complications. Although the surgical procedure is challenging, our encouraging mid‐term results clearly favor and validate this technique. Level of Evidence: Level IV, therapeutic study. See Instructions for Authors for a complete description of levels of evidence.